2003
DOI: 10.1152/ajpcell.00238.2002
|View full text |Cite
|
Sign up to set email alerts
|

P2 purinoceptors regulate calcium-activated chloride and fluid transport in 31EG4 mammary epithelia

Abstract: It has been reported that secretory mammary epithelial cells (MEC) release ATP, UTP, and UDP upon mechanical stimulation. Here we examined the physiological changes caused by ATP/UTP in nontransformed, clonal mouse mammary epithelia (31EG4 cells). In control conditions, transepithelial potential (apical side negative) and resistance were -4.4 +/- 1.3 mV (mean +/- SD, n = 12) and 517.7 +/- 39.4 Omega. cm(2), respectively. The apical membrane potential was -43.9 +/- 1.7 mV, and the ratio of apical to basolateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 53 publications
1
23
1
Order By: Relevance
“…Several physiological responses resulting from P2Y 2 R activation are dependent on the rise of [Ca 2ϩ ] i (e.g. ion secretion, fluid secretion, and vascular cell adhesion molecule-1 expression) (21,54,68); however, our results indicate that P2Y 2 R-mediated increases in [Ca 2ϩ ] i by either calcium released from intracellular stores or calcium influx were not required for sAPP␣ release, because chelation of intracellular calcium with BAPTA had no effect on UTP-induced sAPP␣ release (Fig. 4A).…”
Section: Discussionmentioning
confidence: 99%
“…Several physiological responses resulting from P2Y 2 R activation are dependent on the rise of [Ca 2ϩ ] i (e.g. ion secretion, fluid secretion, and vascular cell adhesion molecule-1 expression) (21,54,68); however, our results indicate that P2Y 2 R-mediated increases in [Ca 2ϩ ] i by either calcium released from intracellular stores or calcium influx were not required for sAPP␣ release, because chelation of intracellular calcium with BAPTA had no effect on UTP-induced sAPP␣ release (Fig. 4A).…”
Section: Discussionmentioning
confidence: 99%
“…To date, investigations into fundamental aspects of mammary epithelial physiology have utilized mouse (5,6) and bovine (41) cell lines. Such studies have determined that fluid secretion across the apical membrane of murine mammary epithelial cells could be stimulated by inhibition of the epithelial Na ϩ channel or activation of the cystic fibrosis transmembrane conductance regulator Cl Ϫ channel (5) or Ca 2ϩ -dependent Cl Ϫ channels coupled to P2Y 2 purinoceptors (6).…”
mentioning
confidence: 99%
“…Such studies have determined that fluid secretion across the apical membrane of murine mammary epithelial cells could be stimulated by inhibition of the epithelial Na ϩ channel or activation of the cystic fibrosis transmembrane conductance regulator Cl Ϫ channel (5) or Ca 2ϩ -dependent Cl Ϫ channels coupled to P2Y 2 purinoceptors (6). More recently, the work of Quesnell et al (41) demonstrated that the electrolyte composition at the apical membrane of bovine mammary epithelial cells has profound effects on the distribution of the tight junction protein occludin.…”
mentioning
confidence: 99%
“…A lower concentration of DIDS (100 μM) almost completely blocked the current as well (data not shown). Since previous studies have shown that DIDS can block P2 receptors [4,8,16,34], the elimination of the ATP-and ADP-induced current by DIDS may result from direct blockade of a P2 receptor rather than a Cl − channel. Therefore, another Cl − channel blocker, 9-AC, was used.…”
Section: Extracellular Atp Activates Outwardly Rectifying Currents Omentioning
confidence: 97%